Implementación del sistema de gestión de seguridad y salud en el trabajo en la empresa comercializadora de mangueras JM de Bogotá D.C. con base en el decreto 1072 del 2015 y el decreto 052 de 2017 (2018)
For the diagnosis we used a checklist delivered by the POSITIVE ARL, which is evidenced the compliance percentage against the SG-SST. A policy is carried out that is approved by senior management and, in conjunction with it, the staff is made aware of the importance of Decree 1072 of 2015, the responsibilities and obligations which must have a commitment on the part of the workers and the employer. A matrix of identification, assessment and evaluation of the risks is made, according to the methodology of Colombian Technical Guide GTC 45, thus generating cause-effect diagrams to understand the root of the risk and thus design corrective controls.